A methods engineering study on First Guarantee Life Assurance Company Incorporated - Edolsa, Charlene (College of Engineering, 2004)
First Guarantee Life Assurance Co., Inc. (First Life) is a family oriented insurance service provider that specializes in both individual and group insurance coverage. Its aim is to be the country's leading life insurance company through excellent service, professionalism and integrity. This study on First Guarantee Life Assurance Co., Inc. was a accomplished through the application of Methods Engineering principles to document procedures, assess the working area and evaluate existing methods, identify possible areas of improvement, and propose recommendations that would feasibly improve work performance and the company service. The group focused on the Group Insurance Department (GID) with the claims process as the core operation under study. Through interviews and observation, the group was able to highlight three main problems, namely : the delays in claims process, delays in customer service and inefficiency in the tracking method for the claims. Minor problems that contribute to the above mentioned such as inequitable accounts distribution, misdirected claims and variable personnel schedule were also noted. Secondary problems like the lack of client feedback and the cluttered work area were also addressed in the paper. The recommendations presented by the group were directed towards expediting the group insurance claims process and improving employee productivity. First, the group strongly suggests the facilitation of the claims processing through the networking all GID computers and connecting the GID to the LIFe system, which is the company's life insurance administration system. This would greatly reduce the amount of paperwork involved in the process and also provide an efficient tracking method for the claims. Document storage would also require less space. Another suggestion is the rating of new accounts based on the number of employees covered by the said account. This way, we can ensure an equitable workload among the Group Insurance Assistants (GIA), improve employee morale, and reduce idle time for the GIA's. Other suggestions that apply to relocation of office equipment (i.e. filing cabinets), installation of a visitor's area, and other layout improvements are integrated into a proposed layout, which is also presented in this project. The recommendations in this study did not aim to reduce costs, but instead designed to standardize the time frame for claims processing and possibly, to expedite it. Returns for the proposed improvements were in the form of greater customer satisfaction and a more customer-friendly service.